Protoplast cultures and protoplast fusion focused on Brassicaceae: A review - B. Navrátilová (Horticultural Science, 2004)
The subjects of this article are protoplast isolations and protoplast fusions, in particular their history, a review of factors influencing the protoplasts isolation and fusion, selection of hybrid plants and utilization of somatic hybrids in plant breed-ing. Somatic hybridization through protoplast fusion can overcome sexual incompatibility among plant species or genera; transfer genes of resistance to diseases (viral, bacterial, fungal), pests, herbicides and others stress factors; obtain cybrid plants; transfer cytoplasmic male sterility or incease content of secondary metabolites in hybrid plants. The article is focussed mainly on the family Brassicaceae because among representatives are significant crops for the human population. Various successful combination of intraspecific, interspecific and intergeneric protoplast fusion were reported between representatives of the family Brassicaceae with the genus Brassica which belonged to the first agricultural crops used for the isolation of protoplast.